Retrieval of Glass Fiber Post Using Er:YAG Laser and Conventional Endodontic Ultrasonic Method: An In Vitro Study. Issue 9 (30th October 2019) - Deeb, Janina Golob; Grzech‐Leśniak, Kinga; Weaver, Colby; Matys, Jacek; Bencharit, Sompop
Abstract: Purpose: To compare the times and temperatures used to remove a glass fiber post from an endodontically treated tooth using erbium‐doped yttrium aluminum garnet (Er:YAG) compared to conventional endodontic ultrasonic method. Materials and Methods: Thirty‐four single‐root human extracted teeth were endodontically treated ex vivo. The post space was prepared to 7 mm in depth and a 11.4 mm glass fiber post was cemented using composite resin cement. Specimens were kept in 100% humidity for 24 hours and then randomly assigned to Er:YAG laser or ultrasonic methods for post removal. The removal time was recorded. Specimens with a fractured post during the removal process were excluded. The temperature on the external surface of the root was measured at the coronal, middle, and apical third portions during the laser or ultrasonic applications from 1 to 10 minutes. Data were analyzed using one‐tailed t‐test and paired t‐test (ɑ = 0.01) for the post removal time and temperature difference, respectively. The specimen surfaces were examined using scanning electron microscopy (SEM). Results: Fifteen specimens were tested in each group. Four specimens were fractured, 2 in the laser and 1 in ultrasonic group. One post was excluded because of laser tip damage. The average removal time were 98 ± 46.1 seconds for Er:YAG laser and 538 ± 215.6 seconds or ultrasonic groups with significant difference between the groups ( p < 0.001). The temperature (°C) ranges measured from 1 to 10 minutes were [24.2°, 27.3°] for laser and [33.0°, 38.0°] for ultrasonic in the cervical area, [22.1°, 24.6°] for laser and [31.0°, 34.6°] for ultrasonic in the middle area, and [24.4°, 27.7°] for laser and [30.3°, 34.1°] for ultrasonic in the apical area. There were significant differences between temperatures for each treatment ( p < 0.001). SEM examination showed no visible damage caused by treatment with Er:YAG laser. Conclusions: Er:YAG laser can remove posts up to 5 times faster than ultrasonic removal method. The laser causes lower temperature increase at the root surface compared to the ultrasonic removal. Er:YAG may be considered as a viable alternative to sonication for post removal.